Is Home-Host Cultural Distance a Risk? Evidence from Outward Foreign Direct Investment by Chinese Enterprises - Su, Hang; Fu, Yao (International Journal of Economics and Financial Issues, 2022)
Cultural distance is always regarded as a “risk” in the decision making of enterprises involved in the outward foreign direct investment (OFDI), however, investment is a powerful driver of productivity growth and increased innovation capacity of enterprises in both countries. Is cultural distance a “risk” ? Using Hofstede's indicators and the Kogut and Singh index (1988), this paper calculates the cultural distance based on six cultural dimensions and further examines the effect of cultural distance on the outward foreign direct investment by Chinese enterprises and its mediating effects on the role of other factors influencing the decisions of multinationals. The results indicate that there is a nonlinear effect of cultural distance and the mediating effect of cultural distance is negative.